Finpron vaikuttavuus: Finpron palveluiden käytön vaikutukset yritysten kansainvälistymiseen ja menestymiseen - Ari Hyytinen; Mika Pajarinen; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2011)
– The study investigates, by using econometric evaluation methods, how the usage of Finpro's (a public agency promoting internationalization of business) services impacts on the internationalization and performance of small and medium-sized firms in Finland. We measure internationalization and firm performance using a number of complementary indicators. The results indicate that being Finpro's customer is positively associated with internationalization when firms establish new subsidiaries abroad or expand the geographical coverage of their foreign operations. There are also indications of a positive association between usage of Finpro's services and exports (measured using a binary export indicator), although the results vary across methods of evaluation. Finpro's customership does not appear to have a statistically significant impact on the share of foreign personnel. Similarly, we do not - in most estimations - find any statistically significant impact on the firm performance. However, different methods of evaluation and data sets produce somewhat inconsistent results. The study also looks at the possible synergy effects of utilizing Finpro's services, and receiving funding from other public organizations (Tekes, Finnvera and the Ministry Employment and the Economy). It turns out that such synergy effects do not seem to exist.
Keywords: H81; L53; O25; 330; internationalization of business; business support system; internationalization; innovation; industrial and employment policies; Finland; Wirtschaftsförderung; KMU; Globalisierung; Unternehmenserfolg; Finnland